Long-term care reform and the labor supply of household members - evidence from a quasi-experiment - Thorben Korfhage; Johannes Geyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Germany introduced a new mandatory insurance for long-term care in 1995. It replaced a system based on means-tested transfers. The new scheme made it easier for households to draw benefits and to organize informal care. We exploit this reform as a natural experiment and examine its effect on the labor supply of caregivers who live in the same household as the care recipient. We find strong negative results for male labor supply but not for women. We conduct a set of robustness tests and our results prove to be stable.
Keywords: J22; H31; I18; 330